Designing a Visual Novel Game to Reflect Stories Set in War - คำเสน รังสิมันตุ์; ปรานต์ เขื่อนแก้ว ปรานต์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research aimed to enhance understanding of war-related issues through the perspectives of those affected and to examine satisfaction with the method of presentation through the development of a Visual Novel game. The sample group consisted of 50 participants from a discussion group of Visual Novel players. The research instruments included: A development plan for a Visual Novel game designed to reflect war-related issues through the perspectives of affected individuals. An assessment form measuring understanding of war-related issues from the perspective of those affected. A satisfaction questionnaire regarding the Visual Novel game as a medium for presenting war-related issues. The statistical methods used for data analysis were mean and standard deviation. The research findings revealed that participants who played the Visual Novel game designed to reflect war-related issues through the perspectives of affected individuals demonstrated a high level of understanding of war-related issues (x̄= 6.82, S.D. = 1.54). Additionally, their satisfaction with the Visual Novel game as a medium for presenting war-related issues was at a moderate level (x̄= 9.95, S.D. = 2.32).